Pengaruh Demand, Orriented Attitude, Dan Orriented Behavior Terhadap Kepuasan Pelanggan Pengguna Shopee - Dwi Iskandar Mizan; Ida Bagus Nyoman Udayana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The development of the internet and technology at this time makes it easier to transact online through web-based shopping sites or e-commerce. E-commerce is currently growing rapidly in Indonesia, with various business applications, one of which is the Shopee application. Shopee brings a large and profitable business opportunity that offers the sale of products or goods and the provision of online services. This study aims to analyze customer demand, shopee application customer behavior and customer satisfaction using the Shopee application. The method used in this research is a quantitative method. Data was collected using library research methods, documentation, and questionnaires. The results of the questionnaire have been tested for validity and reliability have also been tested, in the form of the assumption of normality. The findings of this study indicate that the population in this study are students who use the Shopee application within the UST Faculty of Economics, and the research sample is determined by means of a questionnaire method that has been tested for validity and reliability so that 55 respondents are obtained. The data that has been collected, then carried out data testing, model testing, and SPSS hypothesis testing. Based on the results of the analysis and discussion, the authors conclude that the marketing strategy and service quality together have a positive and significant effect on Shopee purchase satisfaction. Keywords: E-commerce, Shopee, Demand, Oriented Attitude, Behavior Attitude, Customers Satisfaction